Genotype Combination of rs1042044 and rs6458093 in GLP-1R as A Genetic Risk for Osteoporosis in Postmenopausal Iraqi Women - Ammar Kadhim Alzubaidi; Farah Abdulwahab Al-Saadi; Amer Qani Alagele (The Prodia Education and Research Institute (PERI), 2025)
BACKGROUND: Many genetic factors are known to be related to osteoporosis, and currently the role of the glucagon-like peptide-1 receptor (GLP-1R) gene in bone health has been studied intensively. Some variation of this gene, such as rs1042044 and rs6458093, are known to be linked to metabolic diseases and lower bone mineral density, however their specific contribution to osteoporosis remains largely unexplored. Therefore, this study was conducted to investigate the combined genotypic effect of rs1042044 and rs6458093 as a genetic risk factor for osteoporosis in postmenopausal Iraqi women.METHODS: Blood samples from 75 osteoporosis patients and 75 healthy controls, aged 45-85, were collected. DNA was extracted, and a region of GLP-1R gene was amplified by polymerase chain reaction (PCR) and sequenced using the Sanger method to identify polymorphisms. Serum parathyroid hormone (PTH) levels were also measured with chemiluminescent immunoassay (CLIA) methods.RESULTS: Significant differences were observed for age, menopausal age, and PTH levels (p<0.001), but not for Body Mass Index (BMI). While individual SNPs (rs1042044 and rs6458093) showed no significant association with osteoporosis, a specific genotype combination of rs1042044 A and rs6458093 G was found to be a highly significant risk factor for the disease (OR=21.85, p=0.026). Linkage Disequilibrium analysis showed a D' value=0.85 and R²=0.45 between the two SNPs.CONCLUSION: Co-occurrence of the 'A' allele at rs1042044 and the 'G' allele at rs6458093 creates a highly susceptible genetic risk factor for osteoporosis, highlighting a potential novel biomarker for disease risk and providing a benchmark for future studies.KEYWORDS: osteoporosis, postmenopausal, GLP1R, PTH, SNPS